Social and Psychological Capital for the Start-Up of Social Enterprises With a Migratory Background - Modesti, Camilla; Talamo, Alessandra; Nicolais, Giampaolo; Recupero, Annamaria (Frontiers in Psychology, 2020)
The highest number of forcibly displaced people has been currently recorded due to war, poverty and climate change. Recently, a process that recognizes refugees as reliable interlocutors for the improvement of reception policies has started. Refugees are therefore encouraged to start-up social enterprises aimed at fostering newcomers’ social integration to participate to such a phenomenon. Positive Psychology with its focus on human strengths allows to identify the resources that pushed refugees to turn the difficulties they faced during the journey and the resettlement process into resources for themselves and for the resettlement community. The following paper explores in particular the interplay between Social and Psychological Capital that is at the base of a similar social entrepreneurship project through a case study. A qualitative research has been carried out within a Social Enterprise with a Migratory Background to analyze the internal and relational resources that brought founders to start-up the venture. Results show that while Social and Psychological Capital were independently activated to start from scratch in the resettlement community, they occurred in interrelation in a subsequent phase when participants transformed their direct experiences related to migration into the Human Capital of their enterprise.